IMPLEMENTATION OF RESTORATIVE JUSTICE PRINCIPLES IN THE SETTLEMENT OF MISCELLANEOUS CRIMES BY THE POLICE OF THE REPUBLIC OF INDONESIA - Urbanus Situmorang; Irawan Harahap; Indra Afrita (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
From a legal perspective, this article has the potential to reduce the effectiveness of Restorative Justice in building social reconciliation and reducing recidivism. Therefore, there is a need to review the wording of the article to better align it with the principles of Restorative Justice and legal certainty. The purpose of this research is to analyze the legal provisions regarding Restorative Justice in the settlement of minor crimes by the Indonesian National Police and to analyze the application of Restorative Justice principles in the settlement of minor crimes by the Indonesian National Police. The method used is normative legal research. Based on the research results, it is known that the legal provisions for Restorative Justice in the resolution of minor crimes by the Indonesian National Police have a fairly strong normative basis, although they have not been fully codified in the Criminal Procedure Code. The primary legal basis for the implementation of Restorative Justice by the police stems from discretionary authority as specified in the Indonesian National Police Law, which provides room for police officers to act according to their own judgment in the public interest. This regulation was then clarified and reinforced through Indonesian National Police Regulation Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, which regulates the material and formal requirements, settlement mechanisms, and limitations of the application of Restorative Justice. Thus, legally, Restorative Justice in the resolution of minor crimes is a legitimate criminal law policy, based on controlled discretion, and intended to realize substantive justice, efficient law enforcement, and maintain social order. The application of Restorative Justice principles in resolving minor crimes by the police essentially reflects the core values of Restorative Justice, namely the principles of restoration, participation, perpetrator responsibility, a balance between legal certainty and substantive justice, and the protection of human rights. The principle of restoration is realized through efforts to redress the victim's losses and restore social relationships; the principle of participation is realized through dialogue and deliberation between the victim and the perpetrator; while the principle of perpetrator responsibility is reflected in an admission of guilt and a willingness to correct the consequences of the criminal act. However, the implementation of these principles still faces challenges, particularly related to the potential for subjectivity in the use of discretion, inconsistent application across regions, and the risk of neglecting victims' rights if the reconciliation process is not conducted voluntarily and equitably. Therefore, although conceptually and normatively, the application of Restorative Justice by the police is in line with the objectives of modern criminal law, in practice, strengthened oversight and consistency of implementation are still needed to ensure compliance with the principles of legal certainty and equality before the law.